Infrastructural state capacity for democratization? Voter registration and identification in Côte d'Ivoire and Ghana compared. Issue 3 (15th April 2016) - Piccolino, Giulia
Abstract : A large portion of electoral irregularities in developing countries stem from administrative deficiencies, rather than deliberate fraud. This is particularly evident when it comes to voter registration and identification: the quality of a voter list depends on the existence of effective mechanisms to register and identify citizens and electors, which might not be easily at hand in many developing countries. Democratization in these countries has been accompanied by intense polemics about the quality of the voter rolls and the identification of electors, which have threatened democratic consolidation. Biometric technology has been recently heralded as a possible solution, but its effective potential is disputable. In order to understand how problems with registering and identifying voters have affected democratization, this article reviews the contrasting experiences of Côte d'Ivoire and Ghana. In Côte d'Ivoire, the problem of the reliability of the voter register has been entangled since the 1990s with the politicization of the citizenship question. As a consequence, compiling an acceptable voter register has proven extremely difficult and cumbersome. In Ghana, an effective electoral administration has been key to overcoming the mistrust of the political parties about the fairness of the voter process.